Perception of Interdialectal Accommodation by Sellers and Buyers in Sasak: A Sociolinguistic Perspective - Abdul Muhid; Sri Ningsih (Ranah: Jurnal Kajian Bahasa, 2021)
This research focuses on the strategy of communication which was used by the speakers of two different dialects between meriaq-meriku vs meno-mene in Sasak language, especially amongst sellers-buyers in markets domain in central Lombok West Nusa Tenggara. The data were recorded at four markets where the speakers of two different dialects meet. This current result reveals the effective strategy in communication by accommodating each other (sellers-buyers). Further, it elucidates the accommodation pattern strategy in two different dialects which are commonly used by the sellers-buyers in doing transactions. The current researchers composed the data through the interview, direct observation, and recording or note-taking. The method used to reveal the phenomenon is a qualitative method and interpreted the data to meet the qualified result of research. Therefore, the result shows that applying inter-dialectal accommodation is effective. AbstrakPenelitian ini berfokus pada strategi komunikasi yang digunakan oleh penutur dua dialek yang berbeda antara meriaq-meriku vs meno-mene dalam bahasa Sasak, khususnya antara penjual-pembeli di ranah pasar di Lombok Tengah Nusa Tenggara Barat. Data tersebut direkam di empat pasar tempat bertemunya penutur dari dua dialek yang berbeda. Hasil saat ini mengungkapkan strategi yang efektif dalam komunikasi dengan saling mengakomodasi (penjual-pembeli). Selanjutnya diuraikan strategi pola akomodasi dalam dua dialek yang berbeda yang biasa digunakan oleh penjual-pembeli dalam melakukan transaksi. Peneliti saat ini menyusun data melalui wawancara, observasi langsung, dan pencatatan atau pencatatan. Metode yang digunakan untuk mengungkap fenomena tersebut adalah metode kualitatif dan menginterpretasikan data untuk memenuhi hasil penelitian yang memenuhi syarat. Oleh karena itu, hasil penelitian menunjukkan bahwa penerapan akomodasi antar dialek efektif.